Beijing or Shanghai? The strategic location choice of large MNEs’ host-country headquarters in China - Ma, Xufei; Delios, Andrew; Lau, Chung-Ming (Journal of International Business Studies, 2013)
We argue that a multinational enterprise’s (MNE’s) location choice for its host-country headquarters (HCHQ) in the geographic space of the host country is determined by the interplay between the strategic roles of HCHQ in the organizational space of the MNE and the institutional space external and internal to the MNE. We focus on the location choice between Beijing and Shanghai. We test our arguments using data for a sample of Fortune Global 500 corporations in China (1979–2005). This study contributes to international business (IB) research by reinvigorating research on HCHQ. We also complement economic geography research on subnational agglomeration by using an IB perspective with a focus on the institutional idiosyncrasies of cities.